Smart card research and advanced applications : 18 International Conference, CARDIS 2019, Prague, Czech Republic, November 11-13, 2019, revised selected proceedings /: 18 International Conference, CARDIS 2019, Prague, Czech Republic, November 11-13, 2019, revised selected proceedings. ([2020]) - Unknown
No abstract available